Alternaria guilanica sp. nov., a new fungal pathogen causing leaf spot and blight on eggplant in Iran - Poursafar, Alireza; Hashemlou, Esmaeil; Ghosta, Youbert; Salimi, Fatemeh; Javan-Nikkhah, Mohammad (Phytotaxa, 2021)
Eggplant (Solanum melongena L.) is an economically important solanaceous crop in Iran with fruits used for food and traditional medicine. Despite the importance of Alternaria leaf spot and blight disease of solanaceous crops which is commonly seen in the fields, our knowledge about the causal agents on eggplant is limited. In this study, a set of large-spored Alternaria isolates was recovered from eggplant with leaf spot and blight symptoms in Somehsara region, Guilan province, Iran. All recovered isolates shared conspicuous morphological characteristics e.g. production of large, solitary conidia with several transverse disto- and eusepta and long tapering filamentous beak resemble those seen in the members of Alternaria section Porri. Multi-locus phylogenetic analyses based on the internal transcribed spacer region of nrDNA (ITS-rDNA) and parts of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), second largest subunit of RNA Polymerase II (RPB2), translation elongation factor 1-alpha (TEF1-α) and Alternaria major allergen (Alt a 1) gene sequences provided further evidence supporting not only their exact placement in Alternaria sect. Porri, but also in a distinct lineage representing a new species. The new species was named, described and illustrated herein as Alternaria guilanica sp. nov.. The phylogenetic and morphological comaprisions of the new species with other closely related species were also provided. Pathogenicity test conducted for the new strains revealed that they were capable to induce disease symptoms on eggplant leaves under greenhouse conditions, and re-isolation of the inoculated isolates confirmed Koch’s postulates.